Implementation Of The Pentahelix Approach Model Against Development Sustainable Tourism In Bukittinggi City Towards A National Leading Tourism Destination - Siti Fatimah; Jefri Naldi (The Tourism, Heritage and Recreation Sport Center, Universitas Negeri Padang, 2019)
This objective is to describe how the Pentahelix approach model in developing sustainable tourism in the City of Bukittinggi towards a national leading tourism destination. This research is a descriptive research using a qualitative approach. Data were collected through: interviews, observation and literature study. Determination of informants using purposive presentation techniques and key informants of the Head of the Tourism and Culture Office of the City of Bukittinggi. Data analysis by means of: data condensation, data levers and withdrawals. The data validation used source triangulation. The results of the study: (1) The development of tourism in the city of Bukittinggi using the Pentahelix approach model has involved the Bukittinggi City Government, Tourism Academics and Practitioners, Communities and Communities, Business Actors, and the Media. (2) The findings from the field show that the roles and duties of stakeholders are not optimal and (3) The collaboration between stakeholders in the City of Bukittinggi from the results of the research is not synergistic.